Brief Pain Inventory Pain Interference Subscale: Assessing Interference With Daily Living Activities in Older Adults With Multisite Musculoskeletal Pain - Koren, Yael; Leveille, Suzanne G.; You, Tongjian (Frontiers in Pain Research, 2022)
Objectives This study aims to determine domains of pain interference in daily routines assessed using the Brief Pain Inventory, in relation to multisite musculoskeletal pain among older adults living in the community. Design The MOBILIZE Boston Study is a population-based study of 749 adults aged 70 and older. Measurements Chronic musculoskeletal pain was assessed using a joint pain questionnaire and grouped as: no pain, single-site and multisite pain. The Brief Pain Inventory pain interference (PI) sub-scale assessed level of pain interference (0–10 rating) in 7 domains including general activity, mood, walking, work, relationships with people, sleep, and enjoyment of life. Interference ratings were grouped as: none (0), mild (>0 and ≤ 2), and moderate to severe (>2) PI. Results PI was more common among women and those with less education compared to others. Older adults with chronic conditions such as osteoarthritis, depression, spinal stenosis, peripheral artery disease, and asthma/lung disease were more likely than their peers to report PI (p < 0.05). Multisite musculoskeletal pain was strongly associated with pain interference in all domains (p < 0.05). More than half of older adults with multisite musculoskeletal pain reported moderate to severe PI with general activity and walking. The highest prevalence of moderate to severe PI (score >2) in general activity was seen in participants with depression (62%), knee and hand osteoarthritis (71%) and peripheral artery disease (65%). Conclusion Greater attention to PI and PI domains such as general activity and walking, could aid in efforts to reduce the overall impact of multisite musculoskeletal pain among older adults.